Catalytic coating synthesized onto cordierite monolith walls. Its application to diesel soot combustion - Banus, Ezequiel David (2012)
Co,Ba,K/ZrO2 coating onto a cordierite monolith was produced using a sequential process. The first step involved the formation of a ZrO2 layer using a colloidal suspension and the second, the incorporation of active metals. The coating morphology and its physicochemical properties were studied using different characterization techniques. The ZrO2 colloidal suspension and the active ingredients, Co, Ba and K, penetrated through the macropores of the cordierite and their interconnections, both being retained inside the walls and on the external surface. After calcination, the active species were BaCO3, KNO3 and Co3O4. The catalytic performance for diesel soot combustion was analyzed through the loose deposition of soot onto the structured catalyst and the TPO experiments showed a maximum in combustion rate at about 400 ◦C when NO (0.1%) was added. Cordierite monoliths are well known as wall-flow type soot filters and the morphology of their walls provides an optimum substrate for the anchoring of a thin catalytic coating, thus achieving an excellent mechanical stability. Moreover, the catalytic layer also covers internal pores of the channel walls, where some of the soot particles are trapped, enhancing the catalytic activity and preserving most of the original cordierite monolith macroporosity. Therefore, coating cordierite walls with a Co,Ba,K/ZrO2 catalyst constitutes a potential catalytic filter for soot combustion. As the textural properties indicated, no changes in the pore volume were observed after the  incorporation of the catalytic coating, which favors the potential application of this type of monoliths.